Financial Relations Between Central Government and Regional Government in Regional Autonomy - JENERIO, Rio; WATI, Wilna; JAMILAH, Fitria Lailan; TUAHNU, Bernandus; KRISTHY, Mutia Evi (Indonesia Strategic Sustainability, 2023)
Purpose: Law Number 23 of 2014 concerning Regional Government shows a division of authority between the Central Government, Provincial Government, and City Regency Government. Mapping or classification of central and local government affairs is regulated in Article 9 to Article 26.Methodology:The method used in research for writing this paper is to use the type of research